Ergothioneine Modulates Biomarkers of Oxidative Stress, Biochemical Profiles and Rectal Temperatures of Arabian Stallions Following Exercise in A Hot-Humid Environment - Adah, Adakole; Ayo, Joseph; Rekwot, Peter; Aluwong, Tagang; Adah, Deborah (Media Kedokteran Hewan, 2022)
These experiments were performed to determine the effect of ergothioneine (EGT) and environmental parameters on some physiological profiles of Arabian stallions following an 1800 m race in a hot-humid environment. Twelve stallions having a mean weight of 401 ± 7.33 kg and aged 5.28 ± 1.14 years were used as subjects. They were divided into two groups of treated stallions (n = 6) and untreated stallions (n = 6). Group I which was the experimental group was administered with EGT (0.5 mg/kg orally)every week for two months while group II which served as controls was not treated. The temperature and the relative humidity of the experimental site were determined for six days and on the day of the experiment. The temperature-humidity index (THI) was also calculated. Vital parameters and some biochemical parameters of all stallions were determined before the commencement, immediately after, and one hour after the exercise. Some biomarkers of oxidative stress and serum biochemical parameters (aspartate aminotransferase, creatinine and lactate dehydrogenase) of the stallions were also determined.The biochemical parameters were higher (P < 0.05) in the untreated group than in the treated group. The results obtained showed that EGT lowered the rectal temperature and modulated biomarkers of oxidative stress and biochemical profiles.